2016
DOI: 10.3109/14767058.2016.1168800
|View full text |Cite
|
Sign up to set email alerts
|

PlGF in a clinical setting of pregnancies at risk of preeclampsia and/or intrauterine growth restriction

Abstract: Placental growth factor (PlGF) is an angiogenic molecule produced by the placenta and implicated in the pathogenesis of preeclampsia (PE) and intrauterine growth restriction (IUGR). We have evaluated utility and applicability of the PlGF test in a clinical setting of pregnancies at risk of PE or complicated by IUGR in order to assess its relationship with pregnancy outcomes. Seventy-three pregnancies were enrolled between 19 and 35 weeks: 57 pregnancies at risk of PE and 16 at diagnosis of IUGR. Maternal circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
17
2
Order By: Relevance
“…Mijal et al found that the serum level of PlGF in preeclampsia pregnant women was significantly decreased by comparing with normal pregnant women . Cetin I et al found that PlGF level could be used to predict the risk associated with adverse pregnancy such as very low birthweight infants and emergency childbirth . However, our results showed that the level of serum PlGF in preeclampsia group was significantly lower than that in normal pregnancy control group ( P < 0.05) and indicated that placental growth factor was a protective factor for preeclampsia.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Mijal et al found that the serum level of PlGF in preeclampsia pregnant women was significantly decreased by comparing with normal pregnant women . Cetin I et al found that PlGF level could be used to predict the risk associated with adverse pregnancy such as very low birthweight infants and emergency childbirth . However, our results showed that the level of serum PlGF in preeclampsia group was significantly lower than that in normal pregnancy control group ( P < 0.05) and indicated that placental growth factor was a protective factor for preeclampsia.…”
Section: Discussioncontrasting
confidence: 64%
“…8 Cetin I et al found that PlGF level could be used to predict the risk associated with adverse pregnancy such as very low birthweight infants and emergency childbirth. 9 However, our results showed that the level of serum PlGF in preeclampsia group was significantly lower than that in normal pregnancy control group (P < 0.05) and indicated that placental growth factor was a protective factor for preeclampsia. Many researches advocated that low level of PlGF in pregnant women could auxiliary diagnosis preeclampsia by specific binding sFlt-1.…”
Section: Mijal Et Al Found That the Serum Level Of Plgf In Preeclampsiacontrasting
confidence: 60%
“…Elevated levels of sFlt1 sequester VEGF and PlGF to reduce their bioavailability for the membrane-bound receptors and therefore disrupts the angiogenic balance required for proper placental vascular remodeling and angiogenesis (Lecarpentier and Tsatsaris, 2016). Preeclampsia is associated with increased maternal serum levels of sFlt1 and pro-inflammatory TNF-α (Spradley et al 2015), which are linked to maternal hypertensive disorders and fetal growth restriction (Cetin et al 2016; Moran et al 2015). Rodent studies indicate that high fat diets may impair the development of the placental vasculature as evidenced by increased hypoxia in the labyrinth and fetal death was three fold higher in dams fed high fat diets (Hayes et al 2012).…”
Section: Obstetric Complications Associated With Maternal Obesitymentioning
confidence: 99%
“…The algorithm categorizes patients into care levels according to BP and a PlGF cutoff (traffic light) system. In 2017, Cetin and colleagues found that, in those at risk of PE, very low plasma PlGF (<12 pg/mL) was associated with a higher emergency cesarean section rate and earlier delivery . Notably, PlGF seemed to have relatively poor predictive potential for late‐onset disease (sensitivity: 45%), likely rooted in a lesser role for defective placentation in late‐onset pathogenesis .…”
Section: Predictive Tests Utilizing Angiogenic Factorsmentioning
confidence: 99%